(untitled) (Journal of Pakistan Orthopaedic Association, 2014)
Objective: To evaluate the efficacy of positive findings on Transpedicular needle biopsy under fluoroscopic guidance in clinically identifiable cases of vertebral pathologies. Methodology: A total of 55 patients were included in the study, from February 2009 to August 2009, at Shaikh Zayed Hospital, Lahore. 37(67.3%) were male and 18(32.7%) were female. Patients with bleeding diathesis, decreased platelet count (< 75,000), suspected vascular lesion &un co-operative patient were excluded from the study. Patients were followed up till the arrival of biopsy report. Outcome was classified as positive or negative. Positive result was suggested by patient’s clinical course. Insufficient material for reporting was labeled as negative result. Results: The age ranged from 18–80 years. Mean age of patients was 53.54 ±16.99 years. Positive diagnosis was obtained in 38 out of 55(69.1%) patients. The result was negative in 17(30.9%) patients. Out of 38 positive results, 28(50.9%) were of Tumor /Mets, 8(14.5%) of Infection, 2(3.6%) of Osteoporosis. Conclusion: Our results show that image-guided percutaneous transpedicular needle biopsy is 69.1% effective and safe and had no complications. Key words: Positive finding, Negative finding, and Percutaneous transpedicular biopsy